Representation Of Violence In The Film Malignant 2021 - Devina Natalie; Cosmas Gatot Haryono (SEAN Institute, 2024)
Violence refers to physical, verbal, or psychological behaviors carried out to injure or harm others or other beings, including acts of physical abuse, bullying, and warfare. Its impacts often harm societies and individuals, violating human rights principles. Violence can affect the mental and physical conditions of individuals who are victims of it. The purpose of this research is (1) to analyze the meaning conveyed in the film